2014
DOI: 10.1016/j.jaac.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation in Obsessive-Compulsive Disorder and Tourette Syndrome: A Cross-Disorder Study

Abstract: Objective Obsessive-compulsive disorder (OCD) and Tourette syndrome (TS) are heritable, neurodevelopmental disorders with a partially shared genetic etiology. This study represents the first genome-wide investigation of large (>500kb), rare (<1%) copy number variants (CNVs) in OCD and the largest genome-wide CNV analysis in TS to date. Method The primary analyses utilized a cross-disorder design for 2,699 patients (1,613 ascertained for OCD, 1,086 ascertained for TS) and 1,789 controls. Parental data facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 42 publications
10
101
1
Order By: Relevance
“…Our group and others have reported on copy number variations (CNVs) in TD (Fernandez et al, 2012; McGrath et al, 2014; Nag et al, 2013; Sundaram et al, 2010), confirming a role for rare structural variants and showing a trend toward enrichment of de novo events. These findings also provide additional support for the involvement of histaminergic neurotransmission, as well as dopaminergic neurotransmission, in the pathogenesis of TD (Ercan-Sencicek et al, 2010; Fernandez et al, 2012) and suggest a potential overlap with CNVs contributing to other neurodevelopmental syndromes (Malhotra and Sebat, 2012).…”
Section: Introductionsupporting
confidence: 77%
“…Our group and others have reported on copy number variations (CNVs) in TD (Fernandez et al, 2012; McGrath et al, 2014; Nag et al, 2013; Sundaram et al, 2010), confirming a role for rare structural variants and showing a trend toward enrichment of de novo events. These findings also provide additional support for the involvement of histaminergic neurotransmission, as well as dopaminergic neurotransmission, in the pathogenesis of TD (Ercan-Sencicek et al, 2010; Fernandez et al, 2012) and suggest a potential overlap with CNVs contributing to other neurodevelopmental syndromes (Malhotra and Sebat, 2012).…”
Section: Introductionsupporting
confidence: 77%
“…Moreover, although collecting rituals are developmentally normative, with peak age of occurrence about 2 years of age (Evans et al, 1997), children with high levels of fear, shyness, and need for order and predictability may maintain and extend these rituals beyond the age when they are adaptive (Zohar & Felz, 2001). Alternatively, hoarding and autism may be neurodevelopmental consequences of deletions of the same, specific chromosomal regions, as suggested by recent findings (Lionel et al, 2014; McGrath et al, 2014). …”
Section: Discussionmentioning
confidence: 56%
“…Yu and colleagues used polygenic risk scores to identify distinct differences between polygenic risk burden of OCD with and without co-occurring GTS/Chronic Tic Disorder 73 . Also noteworthy is the significant overlap of rare GTS CNVs in loci previously shown to harbour recurrent deletions/duplications in other developmental neuropsychiatric disorders, including autism, ASD, schizophrenia, and epilepsy including 1q21, NRXN1, and 16p13.11 deletions, as well as 22q11 duplications 67,74 . The first reported epigenome-wide association study for GTS, although limited in size, also found significant enrichment among the top hits in genes related to neuropsychiatric and neurological disorders 75 .…”
Section: Shared Genetic Basis With Other Neuropsychiatric and Neurolomentioning
confidence: 99%